326 Generic Prescribing: Where are we now? Prescribing Education is not Enough. (16th September 2019) - Leahy, Aoife; Hynes, Jason; Saif, Kiran; E McCarthy, Christine; Mohd Asri, Nur Atikah; Roy, Amrita; Murphy, Elizabeth; Sebaoui, Salim; Gabr, Ahmed; Zulkifli, Muhamad Daniel; Matti, Basil; O' Hara, Paul; et al.
Abstract: Background: Generic Prescribing is an essential component of prescribing, however it is often overlooked. Use of brand names can led to poor recognition of the correct medications. It can also led to medication error. It is part of the policy of our hospital group that generic prescribing is used at all times. We performed a similar audit in 2018 and 79% of drug kardexes had brand names used. Prescribing education is an integral part of NCHD teaching. We wished to re-audit to determine rates of generic prescribing now. Methods: We reviewed all drug kardexes in 14 wards both medical and surgical in a 48 hour period. Each drug was reviewed and if any prescription had brand names, the entire kardex was deemed non-compliant. Results: 285 Drug kardexes were assessed across 14 separate wards. 41% were on surgical wards, 59% were on medical wards. 31 (11%) of kardexes had complete generic prescribing. Only 3 kardexes on the surgical ward had complete generic prescribing. Conclusion: The low rates of generic prescribing remain an issue in our university teaching hospital. A similar audit was performed in 2018 with average rates of 20% of generic prescribing. This has decreased in the last year. The failure to generic prescribe puts patients at risk of medication error and also increases cost to the HSE. Education on prescribing is part of the NCHD induction, however, 9 months on there continues to be issues with compliance with generic prescribing. Education alone is not enough to improve current practice. The use of e prescribing offers the potential to alleviate this problem.